Pengaruh Profitabilitas, Komite Audit Dan Ukuran Perusahan Terhadap Ketepatan Waktu Pelaporan Keuangan - Annisa, Annisa; Fathiah, Fathiah; Jusmaya, Ance (Universitas Sumatera Barat, 2022)
Study This aim for find proof empirical about influencing factors accuracy timereporting finance company registered banking _ on the Indonesian Stock Exchange, the factors tested in study This that is profitability, Audit Committee, and Company Size. Sample from study This using 60 registered banking companies on the Indonesian Stock Exchange period 2020-2022 taken _ with use purposive sampling method. Method analysis of the data used is analysis quantitative, i.e test assumption consisting of classics from test normality, test multicollinearity and test heteroscedasticity, analysis multiple linear regression, test consisting hypothesis _ from t test, f test as well R2 test. Results study identify that profitability and influential audit committee on precision time reporting finance companym whereas size company No influential on accuracy time reporting finance company registered banking _ on the Stock Exchange Indonesian, On The Ftestisk nown that profitability, audit committe eand size company influential in a way together to accuracy time reporting finance.